RHETORIC OF KITSCH IN THE POST-TRUTH ERA: ‘MEDIA, LITERATURE & CULTURAL STUDIES’ - Lewis, Anupa; Lewis, Shanthi (PEOPLE: International Journal of Social Sciences, 2018)
The current age in its placid reckoning of rib-tickling political spectacle staged on a global scale has been unanimously dubbed the ‘post-truth era’, an adjectival term which has of late gained wide currency and critical sanction in academic spheres of cultural studies, denoting especially a lambasting incline in titillating media buzz, which is blatantly and consciously transferred into the inimical language of caustic ‘kitsch’. As such, the paper at hand as its objective, attempts to theorize and review the petulant phenomenon of kitsch in the post-truth era, by inspecting its varied avatars and inherent complexities from a polemical perspective. In accord, the paper furthermore deems to predicate the cultural bearing of kitsch in the realm of art, aesthetics, politics, media, language, and literature, whereupon the historical origins of the term kitsch has been delineated, i.e. by way of sieving its cultural potency through the following key expressions: ‘bad taste’, ‘bad art’, ‘bad sentiment’.